2 PS + N (Mosquito Nest Eradication and 3R Garbage Management) - Asrianti, Tanti; AB, Ismail; Salma, Andi; Pricilia, Aprilia; Andrea Suci Ramadhani, Syaima; Devyana Putri Tobing, Melisa; Irnith Manggasa, Louis; Aulia, Farah; Dwi Septiani, Tasya (Mulawarman International Conference on Tropical Public Health, 2025)
Background : The main priority problems from the results of the Focus Group Discussion found in Field Learning Experience (PBL) 1 in Tengin Baru Village, especially Hamlet 2, were Mosquito Nest Eradication (PSN) and Waste Management, these problems could potentially cause dengue hemorrhagic fever (DBD). One solution to this problem is the 2 PS + N (Mosquito Nest Eradication and 3R Waste Management) extension program. Objective : The aim of this program is to increase public knowledge and awareness about the dangers of dengue fever and the importance of eradicating mosquito nests Research Methods/ Implementation Methods : This program uses an outreach method in the form of delivering material using PowerPoint delivered by the community health center, as well as filling in pre-test questions and post-test questions to the community in Hamlet 2, Tengin Baru Village. Results : The results of this program were tested using the Wilcoxom test which showed a significant difference between the pre-test and post-test scores, with a p-value of 0.002 < α 0.05 Conclusion/Lesson Learned : It was concluded that of the 18 participants, 12 participants (66.7%) experienced an increase in knowledge after attending the counseling. From this program, a sustainability video was created which is expected to reach participants or the public who were not present during the program implementation.